Iranian productivity in manufacturing sector: empirical evidence using panel estimation techniques - Moradpour, Hamid Reza; Abdul Jalil, Suhaila; Law, Siong Hook (Universiti Putra Malaysia Press, 2013)
Rapid changes in demand and supply models, the byproduct of increasing productivity and competition, cause entrants to pay special attention to the conditions of productivity and environment of the competition. Iranian manufacturing sector faces a major problem where its lack of entrants’ paying attention to productivity issues. Productivity issues cause a waste of resources and wrong entry decisions. This research employs econometrical models to investigate the determinants of productivity. The three productivity equations are estimated into two categories, that is labour-intensive and capital-intensive sub sectors during the period of 1997-2006. The results indicate that productivity, both in labour, capital and joint labour-capital, in twenty one Iranian industries seem to be highly sensitive to investment sales ratio and minimum efficiency of scale. We review performance indicator roles in manufacturing sector in acquiring results of this study. It increases our knowledge about the Iranian manufacturing structure. The importance of this study stems from a desire to formulate industrial policy based on real empirical knowledge rather than on baseless foundations.